Long-term monitoring for the surveillance of the conservation status of Tursiops truncatus in an EU Natura2000 site in the Mediterranean Sea. A pilot study in the Tuscan Archipelago - ARCANGELI, ANTONELLA; CROSTI, ROBERTO; CAMPANA, ILARIA; CAROSSO, LARA; GREGORIETTI, MARTINA; MAINARDI, GIULIA; MAZZUCATO, VERONICA; CASTELLI, ALBERTO (Mediterranean Marine Science, 2021)
A pilot study, using the dataset from the research network ‘FLT Med Net’, which regularly monitors transborder regions in the Mediterranean Sea using ferries as platform for systematic surveys, was undertaken to assess common bottlenose dolphin range and population trends within the Natura 2000 EU marine site “Tutela del Tursiops truncatus”. The site was recently designated by the Tuscany Region (Italy) within the requirement of the EU Habitats Directive. In order to evaluate the conservation status of bottlenose dolphin according to the surveillance scheme of the Directive, two six-year periods (2007-2012; 2013-2018) were compared to assess trends in distribution-occurrence (range); Sightings Per Unit of Effort and Density (population). In total, 18146 NM were surveyed along two fixed transects, recording 90 sightings of Tursiops truncatus and a total of 268 specimens. Between the two periods, slight but not statistically significant differences were assessed, with decreasing trend in range and population of the species; no variation was detected in mean group sizes. Travelling was the most common behaviour, and juveniles were present in 20% of the sightings, concentrated during spring and summer. The consistent FLT Med Net dataset was found to be appropriate to evaluate important parameters for the assessment of trends in the conservation status of Tursiops truncatus at the Natura2000 site scale.